2019
DOI: 10.7189/jogh.09.020403
|View full text |Cite
|
Sign up to set email alerts
|

Presenting complaints and mortality in a cohort of 22 000 adult emergency patients at a local hospital in Nepal

Abstract: Background There is a need to develop sustainable emergency health care systems in low-resource settings, but data that analyses emergency health care needs in these settings are scarce. We aimed at assessing presenting complaints (PCs) and post-discharge mortality in a large emergency department population in Nepal. Methods Characteristics of adult patients who entered the emergency department (ED) in a hospital in Nepal were prospectively recorded in the local emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…A previous survey done in our ED found that AECOPD is a major presentation and the highest 90-day mortality was in individuals with known COPD. 29 Comorbidities like HTN, DM and IHD were present in 18.9%, 7.2% and 2.4% of cases in this study.…”
Section: Discussionmentioning
confidence: 44%
“…A previous survey done in our ED found that AECOPD is a major presentation and the highest 90-day mortality was in individuals with known COPD. 29 Comorbidities like HTN, DM and IHD were present in 18.9%, 7.2% and 2.4% of cases in this study.…”
Section: Discussionmentioning
confidence: 44%
“…The highest mortality was seen in individuals with known chronic lung disease among whom 32% died within 90 days. 25 This suggests that the finding in our study regarding mortality is likely to be underestimated.…”
Section: Discussionmentioning
confidence: 69%
“… 54 In a study where the majority of hospital admissions were attributed to injuries in young adults, respiratory complaints still accounted for 9.2% of total hospital admissions, with COPD or asthma accounting for 0.5% of total hospital admissions. 53 …”
Section: Resultsmentioning
confidence: 99%